Professionally Oriented Practice in Graduate Students in the Context of Networking between University and School - Gutina G.Y.; Yemelyanova I.V. (Psihologiceskaâ nauka i obrazovanie (2007), 2016)
The paper describes the experience of organising professionally oriented practice for graduate students in the context of networking. The model of in-depth professionally oriented practice for students of the master’s programme in Psychology and Education was created and approved by the leading Russian pedagogical universities within the project “Developing and approving new modules of basic master’s programme of professional training in Psychology and Education on the basis of networking between educational organisations providing general and higher education programmes implying in-depth professionally oriented student practice”. The model of in-depth practice is constructed on the grounds of activity- and competency-based approaches. Practical training of graduate students focuses on the structure and content of work functions (actions) defined in the professional standard for educational psychologists.